BEHAVIOUR ANALYSIS OF BRICK MASONRY WALL CONFINED BY REINFORCED CONCRETE FRAME DUE TO LATERAL LOAD - GIAVARI (NIM : 25007002); Pembimbing : Ir. Made Suarjana, MSc., Ph.D, GEMA
Infill wall is usually neglected in structural design of building, because infill wall is considered as non structural element. In reality, infill wall can contribute significantly to stiffness and strength of a building, especially in resisting earthquake load. In this research, brick masonry wall confined by reinforced concrete frame is modeled and analyzed using nonlinear finite element method. The analysis is performed by displacement control for monotonically increasing lateral load to study crack and collapse behaviors of the structural system. The analysis results are compared with experiment results. Infill wall and concrete are modeled as eight nodes hexahedron element. Reinforcing bars are modeled as uniaxial three-dimensional element. Concrete to masonry wall and concrete to reinforcing bar interfaces are modeled as perfect bond without slip or separation. Beside the complete confined masonry model and analysis, simpler models and analysis are performed and verified by manual calculation or compared with beam-column finite element models. The purpose is to calibrate and increase the confident level of the complete confined masonry model. The simpler models developed and verified are simply supported unreinforced concrete beam, simply supported reinforced concrete beam, and reinforced concrete frame without infill wall. Analysis is performed by load control and displacement control methods. The analysis results for simply supported unreinforced and reinforced concrete beam show crack pattern and load displacement curve in agreement with theoretical and hand calculations. Load displacement curve from model of reinforced concrete frame without infill is also in a good agreement with analysis result from beam-column finite element model using different software. For the confined masonry system, the difference of ultimate load from analysis and from experimental result is about 1,4%.